Funäsdalsbadet - Mattsson, Tove (My University, 2025)
This thesis has explored how to situate a complex building, such as a public bath, in challenging terrain, and how this terrain can become an asset to the architecture. Near the Norwegian border in the municipality of Härjedalen lies the small village of Funäsdalen. It is nestled between Lake Funäsdalssjön to the west and Funäsdalsberget to the east. It is a popular holiday destination for outdoor activities during both summer and winter seasons. Nature is the main attraction, offering cycling and hiking trails, snowmobile tracks, and ski systems. Currently, there is no public bath in the area, so both residents and visiting tourists must rely on hotels with swimming facilities. This project has therefore positioned itself somewhere between a swimming hall and a spa, in order to meet the needs of both the local community and schools that require facilities for swim training, as well as tourists, for whom a spa adds a touch of luxury to the vacation experience. The bathhouse is an attempt to merge the striking natural surroundings of the site with the architecture of the building. Ideas about light, darkness, and materiality are grounded in the mountain in which the building is embedded. Research through design has been the main method used, together with texts about atmospheres, bathing and bathing history, along with analyses of buildings situated in similar terrain or with similar functions.
Keywords: Bath, Spa, Steep terrain